Experimental Design of Electrocoagulation and Magnetic Technology for Enhancing Suspended Solids Removal from Synthetic Wastewater - Moh Faiqun Ni'am; Fadil Othman (Chemical Engineering Diponegoro University, 2014)
Design of experiments (DOE) is one of the statistical method that is used as a tool to enhance and improve experimental quality. The changes to the variables of a process or system is supposed to give the optimal result (response) and quite satisfactory. Experimental design can defined as a test or series of test series by varying the input variables (factors) of a process that can known to cause changes in output (response). This paper presents the results of experimental design of wastewater treatment by electrocoagulation (EC) technique. A combined magnet and electrocoagulation (EC) technology were designed to increase settling velocity and to enhance suspended solid removal efficiencies from wastewater samples. In this experiment, a synthetic wastewater samples were prepared by mixing 700 mg of the milk powder in one litre of water and treated by using an acidic buffer solution. The monopolar iron (Fe) plate anodes and cathodes were employed as electrodes. Direct current was varied in a range of between 0.5 and 1.1 A, and flowrate in a range of between 1.00 to 3.50 mL/s. One permanent magnets namely AlNiCo with a magnetic strength of 0.16T was used in this experiment. The results show that the magnetic field and the flowrate have major influences on suspended solids removal. The efficiency removals of suspended solids, turbidity and COD removal efficiencies at optimum conditions were found to be more than 85%, 95%, and 75%, respectively.